Intestine‐Decipher Engineered Capsules Protect Against Sepsis‐induced Intestinal Injury via Broad‐spectrum Anti‐inflammation and Parthanatos Inhibition - Yan Yan; Bin Li; Qiuxia Gao; Miao Wu; Hua Ma; Jiawei Bai; Chengtai Ma; Xinyu Xie; Yuan Gong; Lingqi Xu; Xiaoxue Li; Wei Wang; et al. (Advanced Science)
Abstract Sepsis is a severe systemic inflammatory syndrome characterized by a dysregulated immune response to infection, often leading to high mortality rates. The intestine, owing to its distinct structure and physiological environment, plays a pivotal role in the pathophysiology of sepsis. It functions as the “central organ” or “engine” in the progression of sepsis, with intestinal injury exacerbating the condition. Despite the availability of current therapies that offer partial symptom relief, they fall short of adequately protecting the intestinal barrier. In this study, an advanced nanodrug formulation (OLA@MΦ NPs) is developed by coating macrophage membranes onto polymeric organic nanoparticles encapsulating olaparib. When loaded into pH‐responsive capsules, an intestine‐decipher engineered capsule (cp‐OLA@MΦ NPs) is successfully formulated. Upon oral administration in septic mice, these capsules withstand gastric acid and release their contents in the intestine, specifically targeting injured tissues. The released OLA@MΦ NPs effectively neutralize pro‐inflammatory cytokines via macrophage membrane receptors, while olaparib inhibits intestinal epithelial parthanatos (a form of programmed cell death) by suppressing poly(ADP‐ribose) polymerase 1 (PARP1) activation. This strategy significantly reduces bacterial translocation, slows the progression of sepsis, and enhances survival in septic mice, thus presenting a promising therapeutic approach for sepsis in clinical applications.